2018
DOI: 10.24269/ijhs.v2i1.707
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Pengambilan Keputusan Perawat Dalam Ketepatan Triase Di Kota Padang

Abstract: The absence of guidelines and lack of socialization for regarding triage scale make nurse's ambiguity to determinant the triage scale for patient, thus making the triage judgment innacurate. Inaccurate choosing of the triage scale is the first step that caused long waiting time, affecting the satisfaction rate, patient safety, and even morbidity and mortality. The purpose of this research is to determine the dominant factor of the nurse's clinical decision making on the precision of filling triage scale at Eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
4
Order By: Relevance
“…The accuracy of triage skills in the emergency department is influenced by various factors, namely: student knowledge, skills, education level, length of work, information, and the role of a clinical supervisor (preceptor). The results of research from previous researchers at the Padang City Emergency Room found that knowledge was the dominant factor affecting decision making in triage accuracy with a p-value of 0.012 with OR: 17.8 (Khairina et al, 2018). According to the results of the study (Santosa, 2015), it was found that there was a very strong relationship between knowledge and actions of nurses p = 0.002; r = 0.802.…”
Section: Relationship Between Student Knowledge and The Implementatiomentioning
confidence: 88%
See 1 more Smart Citation
“…The accuracy of triage skills in the emergency department is influenced by various factors, namely: student knowledge, skills, education level, length of work, information, and the role of a clinical supervisor (preceptor). The results of research from previous researchers at the Padang City Emergency Room found that knowledge was the dominant factor affecting decision making in triage accuracy with a p-value of 0.012 with OR: 17.8 (Khairina et al, 2018). According to the results of the study (Santosa, 2015), it was found that there was a very strong relationship between knowledge and actions of nurses p = 0.002; r = 0.802.…”
Section: Relationship Between Student Knowledge and The Implementatiomentioning
confidence: 88%
“…According to Notoatmodjo (2012), knowledge is the result of a person's learning process for something, whether seen, heard, or practiced. Based on the research of Khairina et al (2018), it was found that the knowledge level factor was the dominant factor related to nursing decision-making on the accuracy of filling in the triage scale with a p-value of 0.012 and an odds ratio value of 17.856. [4].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there was a significant correlation between these 2 variables with a p-value of 0.000 and a correlation coefficient of 0.565. While research conducted by Khairina (2018)8 on factors related to nurse decision making in triage accuracy, it was found that the length of work was the most dominant factor with a p-value of 0.012 and an odds ratio value of 17.856.A study presented and reported that nurses had insufficient knowledge about hospital triage, 39.94% of the responses to the knowledge level questions were correct in that study. They concluded their findings that in hospital emergency departments in Iran, nurses were not equipped with triage knowledge.…”
mentioning
confidence: 73%
“…Another study states that the absence of guidelines and socialization regarding filling out the 5-level triage scale raises doubts for triage nurses to determine the patient's triage scale, thus making the triage assessment undertriage and over triage. The inaccuracy of filling in the triage scale is the first step in the occurrence of long waiting times and affects the satisfaction rate and patient safety 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Misalnya seorang ahli komputer yang bekerja pada sebuah perusahaan, atau seorang karyawan yang memiliki kemampuan menggunakan 2 atau 3 bahasa internasional, akan memiliki expert power karena sangat dibutuhkan oleh perusahaannya (Marianti, 2011). Berdasarkan penelitian sebelumnya ditemukan bahwa faktor yang paling dominan mempengaruhi ketepatan pengambilan keputusan perawat adalah pengetahuan yang dimiliki oleh seorang perawat dengan nilai p value 0.012 (Khairina, Malini, Huriani, Dominan, & Pasien, 2018).…”
Section: Expert Power (Ahli)unclassified